Cyclic Triimidazole Derivatives: Intriguing Examples of Multiple Emissions and Ultralong Phosphorescence at Room Temperature. Issue 51 (30th November 2017) - Lucenti, Elena; Forni, Alessandra; Botta, Chiara; Carlucci, Lucia; Giannini, Clelia; Marinotto, Daniele; Pavanello, Alessandro; Previtali, Andrea; Righetto, Stefania; Cariati, Elena
Abstract: The performance of solid luminogens depends on both their inherent electronic properties and their packing status. Intermolecular interactions have been exploited to achieve persistent room‐temperature phosphorescence (RTP) from organic molecules. However, the design of organic materials with bright RTP and the rationalization of the role of interchromophoric electronic coupling remain challenging tasks. Cyclic triimidazole has been shown to be a promising scaffold for such purposes owing to its crystallization‐induced room‐temperature ultralong phosphorescence (RTUP), which has been associated with H‐aggregation. Herein, we report three triimidazole derivatives as significant examples of multifaceted emission. In particular, dual fluorescence, RTUP, and phosphorescence from the molecular and supramolecular units were observed. H‐aggregation is responsible for the red RTUP, and Br substituents favor yellow molecular phosphorescence while halogen‐bonded Br⋅⋅⋅Br tetrameric units are involved in the blue‐green phosphorescence. Abstract : Three triimidazole derivatives were synthesized that display multiple emissions covering dual fluorescence, room‐temperature ultralong phosphorescence (RTUP), and phosphorescence from the molecular and supramolecular units. H‐aggregation is responsible for the red RTUP, Br substituents favor yellow molecular phosphorescence, and halogen‐bonded Br⋅⋅⋅Br tetrameric units are involved in the blue‐green phosphorescence.